Forest Conservation in Flores Island: A Public Administration Review - Nicolaus Petrus Likuwatan Werang; Mia Rizki; Maria Lusiana Florentin Werang; Yeni Husnaeni; Priscilia Yolandasari (Reformasi Administrasi, 2025)
Forest conservation in Indonesia faces significant challenges, specifically on Flores Island, where complex interactions between governance frameworks, traditional practices, and modern conservation approaches influence management outcomes. While existing literature extensively documents conservation initiatives, limited research addresses integrating traditional ecological knowledge with contemporary administrative frameworks. This study examines Flores Island’s institutional and policy mechanisms governing forest management, focusing on identifying structural gaps and proposing integrated solutions. We analyzed policy documents using a qualitative case study approach and employed thematic analysis to evaluate current governance frameworks. Our findings reveal critical deficiencies in cross-sectoral coordination, emergency response protocols, and technological integration mechanisms. The study identified significant policy formulation and implementation gaps, especially in incorporating traditional ecological knowledge and climate change adaptation strategies. The research contributes to public administration literature by proposing an innovative governance framework that balances conservation objectives with socio-economic development. We recommend strengthening institutional frameworks through enhanced stakeholder coordination, sustainable financing mechanisms, and improved emergency response protocols. These findings have broader implications for similar regions facing forest conservation challenges, suggesting that effective conservation requires a comprehensive approach integrating traditional wisdom, modern practices, and robust administrative structures.